Unlocking play willingness: the dual pathways of curiosity drive and downward social comparison in game advertising - Zetian, Dai; Juan, Xue; Jiaxin, Du; Hoe Tan, Wee (Frontiers in Psychology, 2024)
The integrity and clarity of information have long been regarded as the cornerstones of advertising strategy. However, recent game advertising has taken a different approach. Specifically, incomplete game videos, especially those showcasing losing gameplay, are more likely to stimulate players' interest compared to complete videos of winning gameplay. This study, through five experiments, uncovers a dual-pathway mechanism behind this phenomenon. Firstly, information gaps resulting from incomplete videos trigger curiosity drive, compelling viewers to seek more information and reinforcing their willingness to engage in gaming. Secondly, witnessing failures in game demonstrations activates components of downward social comparison and competitive motivation. These findings offer valuable insights into the complex dynamics of game advertising, shedding light on the effects of information gaps, curiosity, and social comparison. They provide valuable implications for advertising strategies within the gaming industry.Advertising, Curiosity Driven, Downward Social Comparison, Need for Cognitive Closure. 2020), and successful behavior tends to induce consumer imitation (Lee et al., 2022).Building upon the analysis mentioned above, this study aimed to uncover the mechanism and rationale behind the use of information gaps and negative gaming experiences in game advertisements. This study seek to address the following questions: Why does the absence of information relative to complete information tend to stimulate players to download the game? And does observing others' gaming failures enhance the viewer's interest in gaming? In this context, this study was grounded in the concept of cognitive closure needs, while also considering downward social comparison as both a moderating and mediating variable, with the goal of revealing the psychological mechanism underlying this phenomenon.The term "curiosity" refers to an innate desire to learn and it is considered to be a relatively stable cognitive tendency (Kashdan et al., 2009). Perceptual and epistemic curiosity are divided into two categories by Berlyne (1960). Epistemic curiosity is the need or desire to learn something in order to dispel uncertainty (